Perspectives on the Self Reflexivity in the Humanities - Matějčková, Tereza; Kolman, Vojtěch (De Gruyter, 2022)
Modernity is the era of the self-made person: the moderns create themselves by self-reflexivity and make their world - society - in their own image. That the social world is reflexive means that its dynamics become independent of its constructors. It is not made of individuals but of a non-subjective communication. The volume analyzes this double reflexivity from an interdisciplinary perspective, focusing both on individual and social narratives.